Republic of Mozambique : Request for a New Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Mozambique's Request for a New Three-Year Arrangement Under the Poverty Reduction and Growth Facility. Mozambique's performance under the authorities' program continues to be generally satisfactory. Real GDP growth remained strong in 2003, real interest rates have declined, the external position has been further strengthened, and major inroads have been made in reducing poverty. The program for 2004 incorporates a number of structural measures aimed at removing remaining obstacles to private sector development and strengthening external competitiveness, which will be followed by additional actions in 2005-06.